Eco-epidemiology of gastrointestinal parasitic infections in captive chimpanzees in Gabon - Mohamed Hassani Mohamed-Djawad; Krista Mapagha-Boundoukou; Neil M. Longo-Pendy; Serge Ely Dibakou; Barthelemy Ngoubangoye; Papa Ibnou Ndiaye; Larson Boundenga (International Journal for Parasitology: Parasites and Wildlife)
This study investigates the influence of abiotic variables (precipitation, soil surface temperature, and soil water content) and intrinsic factors (sex, age class, and social status) on the occurrence of gastrointestinal parasitic infections in two populations of chimpanzees (Pan troglodytes) in Gabon: one in captivity at the Primatology Center of CIRMF (n = 41) and the other in semi-captivity at Lékédi Park (n = 46). A total of 87 fecal samples were analyzed using flotation and sedimentation techniques. Fourteen gastrointestinal parasite taxa were identified, including two novel findings in chimpanzees: Fasciola hepatica and Toxocara sp. The overall prevalence was 85.4 % at the Primatology Center and 95.7 % at Lékédi Park. Binary logistic regression models revealed significant associations between intrinsic traits and parasite occurrence in captive individuals. Juveniles were at higher risk of Balantioides coli infection compared to adults (OR = 7.24; 90 % CI: 2.15–24.3; p = 0.047), while subordinate individuals were less likely to be infected than dominants (OR = 0.08; 90 % CI: 0.02–0.165; p = 0.007). Males were significantly more likely to be infected with strongylid nematodes (Strongylida fam. gen.) than females (OR = 6.58; 90 % CI: 1.90–22.7; p = 0.023). No significant associations were found between intrinsic factors and parasite occurrence in semi-captive individuals. Precipitation was significantly associated with increased infection risks in semi-captive chimpanzees, particularly for Balantioides coli, Entamoeba sp., Mammomonogamus sp., Strongyloides sp., and Trichuris sp. Conversely, in captive chimpanzees, precipitation was negatively associated with Entamoeba sp. and Strongylida fam. gen. Soil surface temperature was inversely correlated with the presence of Balantioides coli, Entamoeba sp., and Mammomonogamus sp. in the semi-captive group. No significant associations were detected between soil water content and parasite occurrence. A Spearman rank correlation analysis revealed a strong positive, though non-significant, relationship between parasite prevalence in soil samples and in captive chimpanzees (ρ = 0.82; p = 0.089).